PENGGUNAAN LEMBAR KERJA SISWA (LKS) MATERI INFORMATIKA DALAM PEMBELAJARAN NEW NORMAL - Yelfiyani Yelfiyani; Supriadi Supriadi (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
This study aims to determined how the use of student worksheets (LKS) on Informatics material during learning in the new normal period. This effect can be seen from the learning outcomes of students in class X MAN 2 Agam. This was because there are problems found where there are still many students who have scores below the completeness criteria, especially in informatics material so that a learning innovation was needed so that students can be active in the learning process, especially through LKS. The type of research that has been used was a quasi-experimental with the population of all X grade students at MAN 2 Agam for the 2020/2021 academic year. Sampling was used purposive sampling technique based on test scores in order to obtain samples in class X. The data of this study were obtained from the final test in the form of objective questions as many as 25 items that have been tested. The data were analyzed using a t-test at a level of 0.05 so that tcount = 0.203 and ttable = 1.68 and dk = 39. Based on these results, the result is that the use of student worksheets (LKS) can affect student learning processes during the new normal. especially based on the results of learning Informatics material at MAN 2 Agam, this is due to reciprocity that can encourage students to understand learning briefly so that the teacher's role as a motivator is carried out properly.